2011
DOI: 10.1038/hr.2011.50
|View full text |Cite
|
Sign up to set email alerts
|

High fitness is associated with a better cardiovascular risk profile in patients with type 2 diabetes mellitus

Abstract: Novel cardiovascular risk markers, such as ambulatory blood pressure (BP) and aortic stiffness, have been proposed. The aim of this study was to investigate the relationship between physical fitness and some of these risk markers in 575 type 2 diabetic patients. In a cross-sectional design, clinical, laboratory, echocardiographic, aortic pulse wave velocity and 24-h ambulatory BP monitoring data were obtained. Fitness was self-reported using a standard questionnaire of daily activities, and then assessed as be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…This is in contrast to studies showing a strong relationship between fitness and incident hypertension in persons with diabetes. 9 This may reflect the fact that the maximal level of METs achieved among participants with diabetes was lower than the METs achieved among those without diabetes. This would attenuate the relationship in participants with diabetes, since METs demonstrate the strongest inverse relationship with incident hypertension at higher levels.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is in contrast to studies showing a strong relationship between fitness and incident hypertension in persons with diabetes. 9 This may reflect the fact that the maximal level of METs achieved among participants with diabetes was lower than the METs achieved among those without diabetes. This would attenuate the relationship in participants with diabetes, since METs demonstrate the strongest inverse relationship with incident hypertension at higher levels.…”
Section: Discussionmentioning
confidence: 96%
“…4 Numerous cross-sectional studies have described a relationship between reduced fitness and blood pressure or hypertension. [5][6][7][8][9] Furthermore, large cohort studies have demonstrated that low fitness precedes new-onset hypertension [10][11][12][13][14][15][16][17][18] even in normotensive populations, 19,20 and among persons with an elevated risk for hypertension. 21 Nevertheless, few studies 13 have examined the effect of demographic factors (age, sex, race) or common comorbidities (obesity, diabetes) on the association between direct measures of fitness and risk for hypertension.…”
mentioning
confidence: 99%
“…Patients assigned to the exercise preceding group will be instructed to walk 30 minutes twice each day or 60 minutes once each day for at least 3 days per week from day 1 to day 28. After the follow-up visits 1 month after enrolment, patients will be instructed to perform physical activity only up to the level of daily life (<4 metabolic equivalents of task [METs]) [10] from day 29 to day 56 until the followup visits 2 months after enrollment. Patients assigned to the exercise lagging group will be instructed to perform physical activity only up to the level of daily life (<4 METs) from day 1 to day 28.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Exercise may improve cognitive function in HF patients through other mechanisms. For example levels of C-reactive protein (CRP), normally an inflammatory cytokine associated with acute injury [ 72 ], are inversely related to amount of physical activity ([ 28 ]; [ 25 , 59 ]). Exercise is thought to reduce activation of the sympathetic nervous system, which in turn inhibits the release of inflammatory markers, including CRP [ 28 ].…”
Section: Reviewmentioning
confidence: 99%